TECHNO- ECONOMIC ANALYSIS OF SOLAR POWER PLANT SYSTEMS TO REALIZE SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Aripriharta Aripriharta; Lia Yunita Sari; Mohamad Rodhi Faiz; Arif Nur Affandi; Suhiro Wongso Susilo; Norzanah Binti Rosmin; Saodah Omar (Jurnal Inovasi Teknologi dan Edukasi Teknik, 2024)
Energy issues related to global warming, the environment, and energy flows are socio-economic challenges in the demand for electrical energy. The demand for electrical energy will increase by around 11-12% in 2025 and 6-7% by 2050 with the Indonesian State Electricity Company being the primary supplier of electrical energy which is mostly sourced from fossil fuels. Applying renewable energy is a solution to reducing dependence on fossil fuels. This study analyzes the technical and economic feasibility of a 46 kWp Solar Power Plant in Beloh village by utilizing PVsyst software. This hybrid system uses 184 solar panels with a capacity of 250 Wp, 2 units of 20 kW inverters, and 224 units of 100 Ah batteries. The results showed that the system output power is 189.25 kWh per day or 69077 kWh/year which will supply the load of 40 houses of 166.82 kWh/ day. In realizing the SDGs, solar power plants can apply SDG 7 with a Performance Ratio (PR) value of 75.7%, SDG 9 regarding industry, innovation, and infrastructure, SDG 11 related to sustainable cities and human settlements. This solar power plant is very environmentally friendly and can reduce carbon dioxide emissions by 1118 tons/25 years. This designed solar power plant system is accompanied by an economic analysis of Net Present Value (NPV) amounting to IDR 404,631,838. Payback Period in the 9th year, Break Even Point (BEP) achieved in the 8th year, and Return on Investment (ROI) of215%.